Clinical Experience of Laser Angioplasty for the Cardiovascular Disease. Issue 1 (1995) - Okada, Masayoshi; Yoshida, Masato; Tsuji, Yoshihiko
Abstract : In recent years, lasers are being utilized in cardiovascular surgery. Since the 1980's we have investigated angioplasty using an Argon laser for patients with obstructive arterial diseases. This technique aims to open the obstructive arterial lumen. Based on the excellent results of experimental studies, the technique has been clinically applied. Laser angioplasty was carried out in 84 patients with stenotic or obstructive lesions occluding more than 75% of peripheral and coronary arteries angiographically. They consisted of 74 cases with intermittent claudication and 10 cases with angina pectoris. Laser angioplasty for the peripheral arterial disease was performed under local anesthesia in the inguinal region under angioscopic guidance. On the other hand, laser coronary angioplasty was simultaneously undertaken at the time of coronary artery bypass grafting for a patient with multiple coronary stenoses. The initial success rate by laser angioplasty for the peripheral artery was 91% in the stenotic lesions and 71% in the obstructive lesions. The cumulative patency rate was 94% in the stenotic lesions and 83% in the occlusive lesions. A follow-up study of 66 months was carried out for patients with clinical success, excluding the cases where an angiogram showed occlusion within 1 week after laser angioplasty. Consequently, excellent long-term results could be clinically obtained. Based on the satisfactory results in the peripheral artery, coronary laser angioplasty was employed in 10 patients with angina pectoris. There were no complications by laser. Thus, the feasibility of laser application was apparently confirmed and laser angioplasty might be recommended for patients with atherosclerotic changes, especially for small arteries.